Open Data in cities 2 . - Berends, Jorn; Carrara, Wendy; Vollers, Heleen (My University, 2020)
On a national level, more and more European Union Member States are recognising the potential value of Open Data and are acting upon it. Open Data portals are in place, increasingly backed by solid Open Data policies. But it is not only the national level that matters. For a successful national Open Data initiative, the whole publication chain should be taken into account. Cities have an important role to play here. Specifically the larger European cities publish a lot of data on topics such as urban planning, tourism, and increasingly real-time data in the transport and mobility area, such as datasets on available parking spots. Moreover, cities also benefit from the use of Open Data to tackle typical urban challenges such as congestion and pollution, and to improve the quality of urban public services and the interactivity between the local government and citizens.
Keywords: Verwaltungsdaten; Kommunalverwaltung; Basisdaten; Urban Governance; Daten; Zugänglichkeit; Versorgung; Technische Infrastruktur; Bildung; Smart City; Internet; Fallbeispiel; Städtevergleich; Open Data; Datenbereitstellung; Internetportal